(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the impact of digital technologies on human cognitive processes in today’s globalized world, which is important for the development of society, and the factors that affect the psychological characteristics of the development of human thinking.